A longitudinal study of Estonian mothers' self-reported language teaching practices and children's language skills. Issue 5 (October 2022) - Tulviste, Tiia; Tamm, Anni
This study explored associations between mothers' language teaching practices and children's language skills concurrently and longitudinally, while also taking into account the children's sex and mothers' education. Estonian mothers of 76 children reported their language teaching practices at child ages 3;0 and 4;0. Children's language comprehension and production were measured via the examiner-administered New Reynell Developmental Language Scales (NRDLS). The results indicated that at Wave 1, girls scored higher on language comprehension and production than boys. Mothers' higher education predicted higher scores on language production. Maternal corrective feedback was a negative predictor of children's concurrent language comprehension. At Wave 2, neither maternal teaching practices, maternal education nor child's sex predicted the language measures of interest. The longitudinal results showed that later language production scores were negatively predicted by mothers' corrective feedback. Yet, the strongest predictors of both language scores were the scores of language comprehension and production measured 1 year earlier. Moreover, maternal language teaching practices at Wave 2 were predicted by mothers' early language teaching practices, but not by children's earlier language skills.